(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Hepatitis C virus (HCV) is a new virus identified in the year l989. Regarding the morbidity & mortality and also for disease burden HCV infection is now an important disease phenomenon worldwide especially among the health care professionals. Laboratory technicians are at increased risk for acquiring blood-borne infections as they have to collect blood samples to find out the disease pathology. The aim of this study is to assess the knowledge and risk behavior on HCV infection among laboratory technicians in a selected army medical unit. Methods: A descriptive cross sectional study was conducted among laboratory technician in a selected army medical unit from 01September 2015 to 31 December 2016. Total 105 participants were interviewed by pretested structured questionnaire. Results: This study explored that 44.8% respondents were in between 31-40 years and 63.8% were educated up to HSC level. All the respondents had overall knowledge about the cause, high risk group and prevention of HCV infection and 20.95% were not aware that water did not transmit HCV infection, 55.24% had no information of vaccination for prevention of HCV infection. This knowledge was gained by majority (62%) of participants from their existing course curriculum. Use of disposable syringe, sterilize instruments, practice of recapping after using needles and their proper disposal were found among all of the respondents and 61% did not habit to use gloves during sample collection due to negligence and lack of time. This study showed that there is an association between level of education and risk behavior (use of gloves) (P<.005). Conclusion: Adequate program on updating knowledge, strict use of gloves, sterile instrument during sample collection will be helpful in minimizing transmission of HCV infection. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 38-42